1996
DOI: 10.1037/0096-1523.22.5.1249
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection analyses of repetition blindness.

Abstract: Three experiments used a signal detection model to demonstrate that repetition blindness (N. Kanwisher, 1987) reflects a reduction in sensitivity (d') for the detection of repeated compared with unrepeated visual targets. In Experiment 1, repetition blindness (RB) was found for rapid serial visual presentation (RSVP) letter sequences, whether the visual targets were specified by category membership (vowels) or as 1 of 2 prespecified letters (e.g., A or O). In Experiment 2, RB was found to a similar degree even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 30 publications
6
56
0
Order By: Relevance
“…A signal-detection analysis was conducted in order to obtain estimates of performance independent of guessing or response biases. A high-threshold alpha model was used to estimate sensitivity, since its assumptions were found to fit the data of previous RSVP detection experiments better than the Gaussian d ¢ model (Kanwisher, Kim, & Wickens, 1996). In addition, the alpha model is more in accord with the subjective reports of most of the participants that they knew the order on some of the trials but on most they did not and had to guess.…”
Section: Resultsmentioning
confidence: 72%
“…A signal-detection analysis was conducted in order to obtain estimates of performance independent of guessing or response biases. A high-threshold alpha model was used to estimate sensitivity, since its assumptions were found to fit the data of previous RSVP detection experiments better than the Gaussian d ¢ model (Kanwisher, Kim, & Wickens, 1996). In addition, the alpha model is more in accord with the subjective reports of most of the participants that they knew the order on some of the trials but on most they did not and had to guess.…”
Section: Resultsmentioning
confidence: 72%
“…For example, the system recognises that the word Bcat^was presented but fails to individuate the two separate presentations. While other explanations for RB have been suggested, such as typenode refractory period (Luo & Caramazza, 1996), and response-level and memory-based explanations (Fagot & Pashler, 1995), these have since been refuted (Chun & Cavanagh, 1997;Kanwisher, Kim, & Wickens, 1996), and thus the type-token individuation failure remains the prevailing explanation.…”
Section: Resultsmentioning
confidence: 99%
“…There are two main motivations for this. First, previous research has shown that RB entails a true change in perceptual sensitivity, rather than just a change in response criterion (Kanwisher et al, 1996). Thus, if the results are related to mechanisms implicating RB, they should be related to changes in perceptual sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Search tasks involving designation of a target set (e.g., vowels or two specific letters) in advance of an RSVP list led to a form of repetition blindness in which detection of two occurrences of the same target within a list was less likely than detection of two different targets within a list (Johnston et al, 2002;Kanwisher, Kim, & Wickens, 1996;Park & Kanwisher, 1994). This task has no postlist recall demands and provides no opportunity for reporting biases such as a bias against reporting an identified item more than once.…”
mentioning
confidence: 99%